Evaluation of ATCO situational awareness in a flow-centric air traffic environment using SAGAT - Pushparaj, Kiranraj (2023)
With current airspace infrastructure being stretched to their limits by the increase in demand for air traffic, Flow Centric Operations (FCO) have been touted to be a possible solution to efficiently manage airspace capacity to support more traffic. However, the novelty of such a concept (assigning flights to Air Traffic Controllers (ATCOs) based on traffic flows) necessitates human factors evaluation in this environment. Particularly, ATCO situational awareness rose to the forefront as a crucial human factor in this arena due to the difference in mental models adopted in this concept. Three fundamental traffic flows, with varying levels of complexity, as determined by a subject matter expert were evaluated for ATCO Situational Awareness. The behavioral results obtained using SAGAT revealed that Situational Awareness for more complex flows were higher, even though participants self-indicated that their situational awareness was lower during the complex flows. This mismatch could be a result of paradoxical complacency during less complex flows, and increased focus during the more complex flows.